Applications of nuclear physics in the diagnosis of cancer - أسماء بنور إمحمد القاضي; زينب سعيد ساسي الحمري (African Journal of Advanced Pure and Applied Sciences, 2025)
This study addresses the vital role of nuclear physics in cancer diagnosis, reviewing the basic physical principles of radiation interaction with living matter and the mechanisms of using radioisotopes in medical imaging. The paper focuses on explaining how nuclear imaging techniques such as positron emission tomography (PET) and single-photon emission computed tomography (SPECT) can be used to detect tumors early and accurately determine their stage of spread. It also reviews the most important radioisotopes used in clinical applications, such as fluorine-18, technetium-99m, and iodine-131, explaining their physical properties and role in diagnosing specific types of cancer, such as thyroid, lung, and bone tumors. The study also highlights the environmental and safety aspects associated with the use of nuclear technologies, including principles of radiation protection, international safety standards issued by the International Atomic Energy Agency (IAEA), and mechanisms for managing medical radioactive waste to reduce radioactive contamination and ensure environmental protection. In conclusion, the results confirm that nuclear physics is an essential tool in modern medicine, thanks to its ability to integrate functional and anatomical information, making it an effective means for early diagnosis and assessing the effectiveness of treatment. The paper also recommends supporting scientific research, developing the infrastructure for nuclear medicine, and enhancing cooperation between physicists and physicians to expand the scope of its applications and improve the quality of healthcare.